Tied-ridging and soil inputs enhance small-scale maize productivity and profitability under erratic rainfall conditions in central Kenya - M., Ndung’u; Mugwe, J.N.; Mucheru-Muna, M.W; Ngetich, F.K.; Mairura, F.S.; Mugendi, D.N (UoEM, 2023)
Deficits in soil moisture and low soil fertility are the major constraints to smallholder farming systems in the SSA (sub-Saharan Africa) region. This study evaluated the effects of tied ridging and selected soil fertility inputs on; soil water content at different depths, maize yields, and economic returns. The treatments were: Tithonia diversifolia + inorganic fertilizer, manure + inorganic fertilizer, inorganic fertilizer, and control with or without tied ridging as the soil water conservation factor. Data were subjected to analysis of variance, and the means were separated using LSD at p ≤ 0.05. Treatments with Tithonia diversifolia or manure combined with inorganic fertilizer with or without tied ridging consistently affected soil water content positively. The effect of tied ridging on soil water content was greater during the short rain season compared to the long rains. In addition, there was evidence that tied ridging and organic soil inputs resulted in greater soil moisture conservation during the critical silking and tasselling maize phenological stages during the short rain season. Treatments had significant effects on grain and stover yields during the long rain 2016 season (p < 0.0001 and p = 0.0477, respectively) and the short rain 2016 season (p < 0.0001 and p = 0.0035, respectively). The highest (4.87 Mg ha− 1 ) maize grain yield was recorded in Tithonia diversifolia plus inorganic fertilizer under tied ridging in the long rain 2016 season, while manure + inorganic fertilizer without tied ridging gave the highest yields (1.27 Mg ha− 1 ) in the short rain 2016 season. The highest net benefits of US$ 1229.90 ha− 1 and US$ 171.57 ha− 1 were recorded under Tithonia diversifolia plus inorganic fertilizer with tied ridging during the long and short rain seasons, respectively. Overall, the best-performing treatments in yields and profitability were those that combined organic and inorganic fertilizers, regardless of the presence or absence of tied ridging. Climate-smart agricultural strategies combining tied ridges and organic inputs should be an integral component of farmer management if losses related to soil fertility and water stress are to be minimized under erratic rainfall regimes in the semiarid farming systems of the SSA region.
Article
Keywords: Climate change; Tied ridging; Soil fertility; Economic returns; Tithonia diversifolia; Soil moisture